Pengambilan Data Cycle Time Menggunakan Aplikasi Seconds Count Pada Kajian Produktivitas Alat Gali Muat PT. X - Bram Lanjaya; Novandri Kusuma Wardana; Bayurohman Pangacella Putra (Retii, 2022)
In the productivity study, there are several things that are done to achieve maximum productivity, including observing loading patterns and cycle time recording. Cycle time recording is usually done manually with stopwatch and stationery. Recording in this way has a fairly large level of measurement error, therefore another method is needed to carry out cycle time measurement activities so as to produce more accurate circulation time calculations, one of which is with the help of the Seconds Count application. The purpose of this study is to identify and analyze the effectiveness of using the Seconds Count application. The use of the Seconds Count application makes it easier to perform data retrieval and analysis of actual front conditions. The results of productivity calculations using data obtained from the Seconds Count application are compared with productivity calculations using Truck Count data and the largest difference is 5.27% so that the use of the Seconds Count application in the study of productivity of digging tools can be concluded to be effective. Keywords: Seconds Count, productivity, cycle time